GRI Index FY11 - World Bank (Washington, DC, 2015)
The response to the global reporting initiative (GRI) indicators provides a brief introduction to the World Bank’s (WB’s) complex suite of activities. The WB consists of the International Bank of Reconstruction and Development (IBRD) and the International Development Association (IDA). Materiality is determined through an assessment carried out based on GRI guidance. The assessment evaluates the risks to the organization, the importance to stakeholders, and the contribution to the organization’s mission. The annual GRI update encompasses global WB operations. WB manages and reports on the buildings that house staff that work on IBRD, IDA, Multilateral Investment Guarantee Agency (MIGA), and Global Environment Facility (GEF) secretariat. GRI indicators for environment, apply primarily to performance of Washington, District of Columbia (D.C.) facilities (which house 60 percent of WB staff) with country office data noted, when relevant. The response attempts to be comprehensive, and provide links to further information in the annual report and throughout the Banks website, where up to date information may be found. The WB reports on a fiscal year basis which extends from June 1 through July 31st. This report covers FY 2011 (July 1, 2010 - June 30, 2011).